Juzentaihoto improves adenine-induced chronic renal failure in BALB/c mice via suppression of renal fibrosis and inflammation - Satoyasu Ito; Eri Manabe; Yi Dai; Masaharu Ishihara; Takeshi Tsujino (Elsevier, 2022)
Renal inflammation and fibrosis are observed in underlying diseases associated with the pathological progression of chronic kidney disease (CKD). The inhibition of renal inflammation and fibrosis is one method to suppress the progression of CKD. Juzentaihoto (TJ-48), a Kampo medicine, effectively relieves chronic wasting diseases and fatigue and has been reported to decrease inflammation. In this study, we investigated whether TJ-48 has a renal protective effect and its underlying mechanism in mice with adenine-induced CKD. BALB/c mice were divided into four groups for examination: (1) control, (2) dietary restriction, (3) adenine, and (4) adenine + TJ-48. Biochemical and histological analyses, gene expression analysis, and complete blood counts were performed. TJ-48 treatment decreased tubular damage and fibrosis. TJ-48 also decreased creatinine levels exacerbated by adenine, suppressed the mRNA expression of tumor necrosis factor-α, chemokine ligand 2, transforming growth factor-β, and kidney injury molecule-1, and decreased the neutrophil/lymphocyte ratio increased by adenine. TJ-48 exerts a renoprotective effect possibly via the suppression of fibrosis and inflammation.